A Reconfigurable Omnidirectional Triboelectric Whisker Sensor Array for Versatile Human–Machine–Environment Interaction - Wang, Weichen; Zhu, Jiaqi; Zhao, Hongfa; Yao, Fei; Zhang, Yuzhu; Qian, Xiankuan; Shu, Mingrui; Wu, Zhigang; Xu, Minyi; Geng, Hongya; Ding, Wenbo; Qu, Juntian (Nano-Micro Letters, 2025)
Developing effective, versatile, and high-precision sensing interfaces remains a crucial challenge in human–machine–environment interaction applications. Despite progress in interaction-oriented sensing skins, limitations remain in unit-level reconfiguration, multiaxial force and motion sensing, and robust operation across dynamically changing or irregular surfaces. Herein, we develop a reconfigurable omnidirectional triboelectric whisker sensor array (RO-TWSA) comprising multiple sensing units that integrate a triboelectric whisker structure (TWS) with an untethered hydro-sealing vacuum sucker (UHSVS), enabling reversibly portable deployment and omnidirectional perception across diverse surfaces. Using a simple dual-triangular electrode layout paired with MXene/silicone nanocomposite dielectric layer, the sensor unit achieves precise omnidirectional force and motion sensing with a detection threshold as low as 0.024 N and an angular resolution of 5°, while the UHSVS provides reliable and reversible multi-surface anchoring for the sensor units by involving a newly designed hydrogel combining high mechanical robustness and superior water absorption. Extensive experiments demonstrate the effectiveness of RO-TWSA across various interactive scenarios, including teleoperation, tactile diagnostics, and robotic autonomous exploration. Overall, RO-TWSA presents a versatile and high-resolution tactile interface, offering new avenues for intelligent perception and interaction in complex real-world environments. Highlights: 1 Dual-triangular electrode layout with MXene/silicone nanocomposite achieves quite competitive omnidirectional force detection (threshold: 0.024 N) and angular resolution (5°) using only two electrodes. 2 Based on a newly designed hydrogel combining high mechanical robustness and superior water absorption, the untethered hydro-sealing vacuum sucker can achieve robust and reversible anchoring on diverse surfaces with a compact structure, maintaining a consistently high anchoring force for more than 200 cycles with a single rehydration. 3 The reconfigurable omnidirectional triboelectric whisker sensor array demonstrates exceptional performance in real-world applications, including teleoperation, adjustable robotic arm palpation, and robotic autonomous environmental exploration, validating its potential as a universal interface for dynamic human–machine–environment interactions.